SPECT miocárdico en preoperatorio de patología vascular periférica. Cambio de conducta en diabético asintomático coronario - Castro M., Gabriel; Rodríguez D., Daniel; Dussaillant N., Gastón; Massardo V., Teresa (Revista Hospital Clínico Universidad de Chile, 2010)
Patients undergoing non cardiac surgery are at high risk of perioperative cardiac events. Those with peripheral arterial disease have important risk factors. Non invasive preoperative cardiac risk radionuclide assessment is an important tool to predict these events as well as to detect unknown coronary artery disease. We present the case of a 79 year old man, with arterial hypertension, Diabetes Mellitus, prior cerebrovascular disease, who was asymptomatic, admitted for diabetic foot surgical therapy. As a part of his preoperative test, a 99m Tc-sestamibi perfusion SPECT was performed, revealing findings compatible with severe coronary disease, confirmed with contrast coronary angiography. A major change in management was achieved with those tests.